Pengaruh Karakter Eksekutif Dan Dimensi Tata Kelola Perusahaan Terhadap Penghindaran Pajak (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Afriyanti, Sharma Aidha (JIFA (Journal of Islamic Finance and Accounting), 2019)
The purpose of the study is to analyze the influence of executive character and corporate governance dimensions on tax avoidance in manufacturing companies that listed on the Indonesia Stock Exchange Period 2012-2016. The samples of this study is 37 companies that selected by using purposive sampling method. The results of this study shows that: Executive characters positive effect on tax avoidance. Independent commissioners not effect on tax avoidance. The audit committee not effect on tax avoidance. Audit quality positive effect on tax avoidance. Keywords: Tax Avoidance, Executive Character, Independent Commissioner, Audit Committee, Audit Quality JEL Classification code: C12, C22, H26, L60